Public administration, social science, and political association - Spicer, Michael W. (1998)
Public administration writers have placed considerabale faith in the power of social science to improve the practice of public administration. This article argues that such faith derives from their vision of the state as a purposive association. However, because we live in what is essentially a civil association rather than a purposive association, there are severe limits on the knowledge that social science can provide for practice. Public administration inquiry, it is concluded, needs to devote more attention to the nature of the civil association in which it operates, particularly in regard to our constitutional system of governance. - Reproduced
Keywords: Public administration